2013
DOI: 10.1088/1748-9326/8/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of future electricity mix alternatives on southwestern US water resources

Abstract: A climate driven, water resource systems model of the southwestern US was used to explore the implications of growth, extended drought, and climate warming on the allocation of water among competing uses. The analysis focused on the water benefits from alternative thermoelectric generation mixes, but included other uses, namely irrigated agriculture, municipal indoor and outdoor use, and environmental and inter-state compact requirements. The model, referred to as WEAP-SW, was developed on the Water Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…cooling water volume per electrical energy output) based on reported values from primary literature sources [25,10]. This compilation of water use rates has been central to most recent studies evaluating cooling water use at the operational phase of power production [22,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. It characterizes power facility cooling water consumption and withdrawal rates based on fuel, cooling system, and prime mover configuration for a small sample of generators (on average four facilities per technology classification) reflecting the best available data at the time of publication [10].…”
Section: Introductionmentioning
confidence: 99%
“…cooling water volume per electrical energy output) based on reported values from primary literature sources [25,10]. This compilation of water use rates has been central to most recent studies evaluating cooling water use at the operational phase of power production [22,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. It characterizes power facility cooling water consumption and withdrawal rates based on fuel, cooling system, and prime mover configuration for a small sample of generators (on average four facilities per technology classification) reflecting the best available data at the time of publication [10].…”
Section: Introductionmentioning
confidence: 99%
“…Showing that low-carbon and low-water electricity production can go hand-in-hand, it drew substantially on the findings of the energy-water modeling and related research of Macknick et al (2012b), Sattler et al (2012), Clemmer et al (2013), Flores-López and Yates (2013) and Yates et al (2013aYates et al ( , 2013bYates et al ( , 2013c.…”
Section: Impact Of the Special Issuementioning
confidence: 99%
“…This issue provides perhaps the most comprehensive and integrated effort to assess the water implications of electric power generation in the U.S., both at the national level and also with a high enough level of spatial resolution to assess watershed-level impacts. This issue includes the following sets of analyses: (a) a review of water factors from the primary literature [23 ] and comparison of reported and calculated water use [22]; (b) description of a linked energy and water modeling framework (ReEDS and WEAP) [44]; (c) modeling of low carbon electricity futures [37], with assessment of the water impacts of those scenarios at the national and regional level [34 ]; and (d) linking the results of the electricity scenarios with models of regional water systems for the southeastern U.S. [31,43] and southwestern U.S. [32,42].…”
Section: Long-term System-level Trends In Water For Energymentioning
confidence: 99%